A region at risk the human dimensions of climate change in Asia and the Pacific. (Metro Manila, Philippines Asian Development Bank, 2017)
Asia and the Pacific continues to be exposed to climate change impacts. Home to the majority of the worlds poor, the population of the region is particularly vulnerable to those impacts. Unabated warming could largely diminish previous achievements of economic development and improvements, putting the future of the region at risk.The report discusses the most recent projections pertaining to climate change and climate change impacts in Asia and the Pacific, and the consequences of these changes to human systems, particularly for developing countries. It also highlights gaps in the existing knowledge and identifies avenues for continued research.
Keywords: Climatic change -- Pacific Area; Environmental economics; Electronic books